Tissue banks. World experience. The history of development and current approaches - A. S. Mironov; N. V. Borovkova; M. S. Makarov; I. N. Ponomarev; Yu. V. Andreev (Трансплантология (Москва), 2021)
The article outlines the main stages of the formation, development and specialization of medical institutions associated with the harvesting and procurement of allogeneic tissues, considers the global practice in the field of tissue institutions, taking into account medical and legal aspects. In the second half of the XX century, the tendency has developed towards the consolidation of tissue banks and the expansion of their functional capabilities within individual states. The development of this trend in the late XX - early XXI centuries led to the establishment of international tissue banking associations. The goal of international associations of tissue banks has been to develop cooperation, standardize procedures at all stages of tissue harvesting and procurement, and form an effective legislative framework. In the Soviet Union, the procurement of donor tissues was widely developing, but in the 90s, in our country there was an abrupt decline in this field. To date, in Russia, the harvesting and procurement of allogeneic tissues is carried out in only a few institutions; the development of tissue institutions is difficult due to the lack of an adequate legal framework. The article proposes to legally differentiate the concepts of "organ transplantation" and "tissue transplantation"; as an example, the US experience in this area is discussed.